The Utilization Of The Animiz Application As A Media For Arabic Language Learning On Students - Durrotul Hikmah; Garik Petoukhoff; Jessica Papaioannou (Journal International of Lingua and Technology, 2022)
The lack of comprehension and interest of students in the material being taught is still felt today. Therefore, a breakthrough was created in the form of procurement of educational technology in the form of an applicative media called Animiz Animaker, especially in the realm of learning Arabic. The purpose of this research is to increase students' interest in learning Arabic by utilizing the Animiz Animaker application. Arabic, which is often considered difficult by many people, may become a subject that is considered fun after the application of the Animiz Animaker application. The form this research methodology is to use quantitative methods using an instrument in the form of research questionnaires distributed to schools that are the object of research. The population in this study were students of Islamic Elementery, and then the sample was selected using a random sampling technique or where the sample was chosen at random. The sample size was found to be 30 students. The results of this study indicate that there is an increase in students' interest in learning Arabic by utilizing the Animiz application at Islamic Elementery. Based on the results of this study, it is known that the use of the Animiz application in learning Arabic can be applied, so it is highly expected that the patience of the educators to prepare this as well as possible.